Self-rated health of population in southern China: association with socio-demographic characteristics measured with multiple-item self-rated health measurement scale - Feng Liyi; Zhang Jinhua; Xu Jun; Qiu Jincai (BMC, 2010)
Abstract Background Self-rated health (SRH) status has been increasingly acknowledged as a valid and appropriate indicator of public health and chronic morbidity. However, limited research was conducted in China due to the different culture and socioeconomic situations. The aim of this study is to assess the SRH status of the population in Southern China using multiple-item SRH measurement scale (SRHMS). Socio-demographic characteristics including sex, age, marital status, education, and income are considered variable in this survey. Methods A cross-sectional survey was conducted in a total of 8400 community residents of 14 years old and over in Southern China. SRH status was measured using SRHMS with a stratified sampling approach, and compared between different subgroups with t-test and one-way analysis of variance (ANOVA). Results Totally 8400 subjects were recruited in this study and 80.96% (6801) responded to the survey. The mean score for SRHMS dimensions ranged from 66.16 ± 20.65 (mean ± sd) for positive emotion (M2) to 92.14 ± 14.06 for daily physical activities (B2). Results showed that SRHMS scores for women, elderly men, low education level, low income, divorced, separated or widowed and suburban residents in Southern China were significantly lower than other subgroups (P < 0.05). Conclusions In this study, using SRHMS we assessed the association of SRH with socio-demographic characteristics including sex, age, marital status, education, and income in Southern China. The performance of the questionnaire in the large scale survey is satisfactory and provides a large picture of SRH status in Southern China. Our results indicate that women, elderly men, low education level, low income, divorced, separated or widowed and suburban residents in Southern China suffer from relatively poor SRH status.